PELAKSANAAN KEWENANGAN KEPALA DESA DALAM PEMBERHENTIAN PERANGKAT DESA PANGKALAN BARU KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2020 - Saktio Aditia; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This thesis discusses the Implementation of the Authority of the Village Head in Dismissing Village Apparatus of Pangkalan Baru, Siak Hulu District, Kampar Regency in 2020. The purpose of this study was to find out why the process of dismissing village officials was not based on Permendagri Number 67 of 2017 and to find out why the Village Head abused his authority in the process of dismissing the new base village apparatus in 2020. This research uses a qualitative method with a descriptive type in order to produce a systematic and objective description of the facts and elements in the research. The result of this study is that the researcher found that the process of dismissing village officials was not based on Permendagri Number 67 of 2017, the Village Head justified the dismissal of the village apparatus and did not violate existing regulations, this dismissal was the policy of the Village Head. The dismissal of the village apparatus is also not arbitrary, there are reasons why this village apparatus is dismissed. Keywords: Authority, Village Head, Village Apparatus